Organizational Culture and LeadershipOrganizational Culture and Leadership, by ScheinEdgar H.. San Francisco: Jos-sey-Bass, 1985, 358 pp., $21.95, cloth. - Tierney, William G. (Academy of Management Review, 1986)
The article presents a review of the book ?Organizational Culture and Leadership,? by Edgar H. Schein.